Category of the type «Manager» in scientific research - Кучма, Ольга Леонідівна; Сіньова, Людмила Миколаївна; Кузьменко, Галина Валентинівна (My University, 2021)
Стаття присвячена огляду наукових праць у правовому статусі керівників різних рівнів, їх класифікації та взаємодії різних ланок у структурі роботодавця. Дослідження показує, що в сучасному світі пріоритетними є співробітники, наділені лідерськими якостями. Доведено важливість стабільності бізнес-процесів у побудові чіткої системи взаємодії керівників різних центрів відповідальності

The article is devoted to review of scientific works within legal status of managers of different levels, their classification and interaction of different links in the structure of an employer. The research reveals that employees who are endowed with leadership qualities are in priority in modern world. Importance of stability of business processes in building a clear system of interaction of managers of different liability centres is proven
Keywords: top-manager; working owner; top manager; quality of atop-manager; responsibility of a leader; топ-менеджер; працюючий власник; якість топ-менеджера; відповідальність лідера